ACIDOGENIC FERMENTATION OF LIGNOCELLULOSIC SUBSTRATE WITH ACTIVATED SLUDGE - Qi, B.; Aldrich, Chris; Lorenzen, L.; Wolfaardt, G. (Taylor and Francis Inc, 2005)
The lignocellulosic residues accumulated in municipal sold waste and agro-residues represent potential organic fractions preferably to be treated by anaerobic digestion in an energy recycle and/or value-added-product-type solid waste disposal system. Hydrolysis and acidification are predominant reactions in organic fermentation. Owing to the complicated physiochemical structures, the initial hydrolysis and acidification of the lignocullulosic residues into soluble forms are critical to the anaerobic digestion of the residues. This research focused on the promotion of solid-state acidogenic fermentation of two natural lignocellulosic residues in a pure form from the tobacco industry and urgan turf grass by a combined pretreatment and thermophilic co-digestion with concentrated activated sludge from a biological municipal wastewater treatment plant. Laboratory-scale experiments were conducted in a batch and semi-continuous mode, with and without leachate recirculation. The results showed that the mechanophysicochemical pretreatment (roll milling-freezing-thawing-alkali wetting agent), followed by thermophilic co-digesition with activated sludge, substantially increased the solubility and fermentation efficiency of the natural lignocellulosic residues, leading to value-added utilization of these residues. In addition, leachate recycling appeared to be beneficial to acidogenesis.